(untitled) (Delito y Sociedad, 2024)
Cultural criminology is a perspective that investigates the interplay between individual experience, cultural meanings, and the social power present in transgression and social deviation. From this viewpoint, the idea of offenders as essentially deviant subjects devoid of any affiliation with open society is questioned, proposing the possibility of thinking about blurred cultural boundaries, mainstream practices and shared understandings about social reality. Thus, the notion of conventionalism becomes relevant, which is observed in behaviors and attitudes consistent with established norms. From the point of view of cultural criminology, this article explores the notion of conventionalism in offenders, for which the account of a young man imprisoned during covid-19 is presented as a case study, collected through an semi-structured interview in which the following topics were addressed: identity, family and couple, politics and social position, consumerism, and perception of the future from a conventional perspective, to conclude with a discussion dedicated to social control and crime. This review allows to establish humanizing bridges with the phenomenon of “common crime”, thus allowing to understand it from different perspectives.